1994
DOI: 10.2166/wst.1994.0327
|View full text |Cite
|
Sign up to set email alerts
|

Runoff pattern of pesticides from paddy fields in the catchment area of Rikimaru reservoir, Japan

Abstract: Patterns of runoff behaviours in concentration and loading of pesticides from paddy fields have been intensively observed in the catchment area of Rikimaru Reservoir, mainly during the regular application period of fungicide during the summer. The runoff characteristics of three pesticides (pyroquilone, isoprothiolane and flutolanil) from paddy fields to the drainage river differed from one another due to their water solubilities. The linear correlation between the water solubilities and the amounts of pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Pesticide occurrence in water supplies is a concern for water-quality assessment, since a huge number of pesticides are widely used in agriculture (Nagafuchi et al 1994;Kimbrough and Litke 1996). Pesticides are a group of hazardous materials with potential risk to human health (Ayranci and Hoda 2005).…”
Section: Pesticidesmentioning
confidence: 99%
“…Pesticide occurrence in water supplies is a concern for water-quality assessment, since a huge number of pesticides are widely used in agriculture (Nagafuchi et al 1994;Kimbrough and Litke 1996). Pesticides are a group of hazardous materials with potential risk to human health (Ayranci and Hoda 2005).…”
Section: Pesticidesmentioning
confidence: 99%
“…e potential for them being discharged into public water is another factor that should be taken into account. Previous reports based on eld observation 10,[16][17][18] and model simulation 7,18,19) have indicated that surface runo during the earlier period of high pesticide concentration in paddy water causes a signi cant loss of pesticides from rice paddies. In terms of the e ect on acute toxicity to an aquatic ecosystem, the estimation of the short-term discharge (for example, daily or hourly discharge) in a high runo period is important.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, a number of pesticides have been detected in river and lake systems especially in the period shortly after herbicide application in the fields. [1][2][3][4][5] The impact of pesticides in surface water on fish, algae and aquatic plants has been reported. 6,7) Therefore, public concern about the low-dose, longterm effect of these pesticides on aquatic flora as well as human health is increasing.…”
Section: Introductionmentioning
confidence: 99%